Something upstairs - Avi, 1937- (New York : Orchard Books, 1988)
When he moves from Los Angeles to Providence, Rhode Island, Kenny discovers that his new house is haunted by the spirit of a black slave boy who asks Kenny to return with him to the early nineteenth century and prevent his murder by slave traders.
Keywords: Ghosts -- Fiction; Time travel -- Fiction; Slavery -- Fiction